Implementation of Policies for the Prevention and Handling of Sexual Harassment Against Women in Sidenreng Rappang Regency - Fitriani Herman; Erfina; Muliani Samiri; Sundari Kawaru (WISE Pendidikan Indonesia, 2026)
Sexual harassment against women is a public issue that requires the implementation of effective policies at the local government level. The Indonesian government has enacted Law No. 12 of 2022 on Criminal Acts of Sexual Violence as the legal basis for the prevention and handling of sexual violence. This study aims to analyze the implementation of policies for the prevention and handling of sexual harassment against women in Sidenreng Rappang Regency carried out by the Office of Community Empowerment, Village, Women and Child Protection (DPMDPPA), as well as to identify the supporting and inhibiting factors in its implementation. This study uses a qualitative descriptive approach with data collection techniques in the form of in-depth interviews, non-participatory observation, and documentation studies. Informants were determined using the snowball sampling technique. Data analysis was conducted using the interactive analysis model of Miles, Huberman, and Saldana with the policy implementation theoretical framework of George C. Edwards III, which includes the aspects of communication, resources, implementer disposition, and bureaucratic structure. The results of the study show that policy implementation has been carried out through cross-sector coordination and supported by the commitment of officials, but still faces obstacles in the form of limited resources, supporting facilities, and social stigma that affects case reporting. Therefore, it is necessary to strengthen coordination and improve.